Brill's Companion to the Legacy of Greek Political Thought - Carter, David,; Foxley, Rachel,; Sawyer, Liz, (Brill's Companions to Philosophy ;, 2025)
A wealth of political literature has survived from Greek antiquity, from political theory by Plato and Aristotle to the variety of prose and verse texts that more broadly demonstrate political thinking. However, despite the extent of this legacy, it can be surprisingly hard to say how ancient Greek political thought makes its influence felt, or whether this influence has been sustained across the centuries. This volume includes a range of disciplinary responses to issues surrounding the legacy of Greek political thought, exploring the ways in which political thinking has evolved from antiquity to the present day.